Nanotechnology applications in Ulcerative colitis: recent developments and future directions - Silveira da Silva, Adrine; Portela Balbé, Fábio; Fontana, Tuyla; Fernandes, Liana da Silva; Rech, Virginia Cielo (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Ulcerative colitis is characterized by prolonged, lasting inflammation in the colon, leading to immune system alterations and ongoing inflammation. Despite being one of the most common intestinal diseases, its cause is still unclear and involves multiple pathophysiological factors. Common symptoms include ulcers, bleeding, diarrhea, and abdominal pain. Identifying the clinical condition involves the process of differential diagnosis, which includes conducting endoscopic examinations and biopsy. Treatment aims to manage symptoms and minimize remaining inflammation to prevent future relapses. Multiple pharmaceuticals are accessible, although their efficacy is restricted, and they may cause significant adverse reactions. Scientists have discovered that modified liposomes and co-hybridized phospholipid vesicles could be used to treat ulcerative colitis. These compounds are delivered directly to specific cells and can be released over time. Enclosing bioactive chemicals within proteins is also highly efficient. Currently, these systems are under development and face challenges. This review provides up-to-date research findings on using nanotechnology to treat ulcerative colitis.